Um novo biocimento de hidroxiapatita e β-fosfato tricálcico promove a ativação de osteoblastos in vitro e a regeneração óssea de defeitos críticos em calvária in vivo - Silva, Cristiane Maria Pereira da (2023)
Bone is the second most common tissue transplanted, so the development of synthetic grafts is crucial for replace and overcome limitations associated with autogenous grafts. Among synthetic bone grafts, calcium phosphate bone cements have generated a great deal of interest for the advantages of bioactivity, easy shaping, osteconduction, osteoinduction, drug-delivery and selfsetting at room and body temperature. The aim of this work was to evaluate osteoblasts activation, biocompatibility in subcutaneous tissue and osteoconductive potential of a new biocement (BC) of hydroxyapatite and β-tricalcium phosphate of rapid hardening and low production cost. The activity of murine osteoblasts (OFCOL II) was performed by quantifying the levels of bone alkaline phosphatase (ALK) in the culture medium, after 72 hours of incubation with the groups: direct and indirect contact with the BC and DMEM group (C-). For the in vivo assessments, 60 male Wistar rats (250-350g) participated in two experimental protocols. In the first protocol, empty (C-) and BC-filled tubes were implanted in subcutaneous pockets on the back of 24 rats. After 15, 30 and 60 days, the animals were euthanized for removal of tissues in contact with the implants and subsequent histopathological evaluation. In the second protocol, 2 critical defects were performed in the calvaria of 36 rats, therefore, each animal received two different types of treatment. The treatments were classified as: clot group (COA); autogenous bone group (OsA); biocement group (BC) and biocement/bovine collagen membrane group (BCM). At 30, 60 and 90 days, the animals were euthanized to remove bone tissue that was evaluated by histology and histomorphometry, assessing the area of bone neoformation, amount of residual BC and the formation of loose connective tissue (FCT). Kidney, liver and spleen were also removed for analysis of morphological parameters of toxicity. The results show that FAO levels were higher in all groups in contact with BC compared to the control group, especially in the direct contact group. According to the results for the evaluation of biocompatibility in subcutaneous tissue, there were no significant differences between groups C and BC regarding the intensity of the inflammatory infiltrate in the three periods evaluated. In both groups, between 15 and 30 days, the inflammatory infiltrate went from intense to mild. In the rat calvarial critical defect model, the groups presented the following results for bone neoformation: OsA > BCM > BC = COA (30 days); OsA > BC = BCM > COA (60 days); OsA = BC = BCM > COA (90 days). In the BC and BCM groups, there was a 46.31% and 32.86% increase in bone neoformation, respectively, between 60 and 90 days. For amount of residual BC: BC = BCM (30 days); BC > BCM (60 days); BC = BCM (90 days). In the BC group, the amount of residual BC decreased by 17.6% from 60 to 90 days. In the BCM group, there was a 19% decrease between 30 and 90 days. For TC formation: COA > BC = BCM > OsA (30 days); COA > BC = BCM = OsA (60 days and 9 days); COA > BC = BCM = OsA (90 days); COA > BC = BCM = OsA (60 days and 9 days). For all results, p<0.05 was considered. Finally, no morphological changes of toxicity were observed in the kidney, liver and spleen of animals treated with CB. In conclusion, CB was able to activate osteoblasts in vitro, showed biocompatibility in subcutaneous tissue, promoted osteoconduction in critical defects and did not induce morphological changes in liver, kidney and spleen. In critical defects treated with BC, the presence of the bovine collagen membrane did not promote an increase in bone neoformation after 30 days and did not influence a lower formation of TC. This result demonstrates the ability of BC as a physical barrier against TCF invasion and signals its promising use as a biomaterial in dentistry.